Designing L21-strengthened Al-Cr-Fe-Ni-Ti complex concentrated alloys for high temperature applications. (1st June 2021) - Kim, Woo Chul; Na, Min Young; Kwon, Heoun Jun; Na, Young Sang; Won, Jong Woo; Chang, Hye Jung; Lim, Ka Ram
Abstract: For alloys with nanoprecipitate/matrix microstructures, the lattice coherency between the two phases plays an important role in determining the mechanical performances at high temperature. In this work, we systematically investigate the Alx Cr13.3 Fe71.5-x Ni11.2 Ti4 (x=8, 10, 12, 14, 16 at%) complex concentrated alloys with an aim to enhance the lattice coherency between the BCC matrix and L 2 1 precipitate. The precipitate microstructures, lattice misfit and the resultant coherency strain evolution are comprehensively studied. With increasing Al from 8 at% to 16 at%, the interfacial structure gradually transforms from semicoherent to fully coherent interface by the decrease in precipitate size and lattice misfit, which leads to the stronger elastic interaction between the matrix and precipitate. Meanwhile, the crystal structure of precipitate is slightly distorted from cubic to tetragonal. The yield strength of alloys at room temperature continuously increases with the addition of Al by the solid-solution strengthening and precipitation hardening effect. Here, the mechanism of precipitation hardening changes from Orowan process to coherency strengthening. Interestingly, the strengthening effect by Al addition is further amplified in the tensile test at 700 °C. The higher degree of lattice coherency and the distorted structure of the precipitate resulting from the Al addition lead to the effective strain transfer and the stronger precipitate, respectively. Therefore, the Al16 Cr13.3 Fe55.5 Ni11.2 Ti4 alloy exhibits an excellent combination of yield strength (400.8 MPa) and ultimate tensile strength (572.9 MPa). These values are much higher than those of the previously reported nanoprecipiate-strengthened alloys, suggesting that the alloy is highly promising as high temperature structural applications. Graphical abstract: Image, graphical abstract